2016
DOI: 10.1038/nature19846
|View full text |Cite
|
Sign up to set email alerts
|

Tidal evolution of the Moon from a high-obliquity, high-angular-momentum Earth

Abstract: In the giant impact hypothesis for lunar origin, the Moon accreted from an equatorial circumterrestrial disk; however the current lunar orbital inclination of 5 • requires a subsequent dynamical process that is still debated [1][2][3] . In addition, the giant impact theory has been challenged by the Moon's unexpectedly Earth-like isotopic composition 4, 5 . Here, we show that tidal dissipation due to lunar obliquity was an important effect during the Moon's tidal evolution, and the past lunar inclination must… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
107
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 129 publications
(114 citation statements)
references
References 53 publications
3
107
2
2
Order By: Relevance
“…Alternatively, a synestia could be brought below the CoRoL by removing AM from the structure by tides, interactions with the host star [ Murray and Dermott , ], or three body interactions with the host star and a moon [ Goldreich , ; Touma and Wisdom , ; Ćuk and Stewart , ; Wisdom and Tian , ; Ćuk et al , ; Tian et al , ]. A significant reduction of AM by tides takes 10 3 –10 9 years, depending on the mechanism, which is generally greater than the radiative cooling timescale.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, a synestia could be brought below the CoRoL by removing AM from the structure by tides, interactions with the host star [ Murray and Dermott , ], or three body interactions with the host star and a moon [ Goldreich , ; Touma and Wisdom , ; Ćuk and Stewart , ; Wisdom and Tian , ; Ćuk et al , ; Tian et al , ]. A significant reduction of AM by tides takes 10 3 –10 9 years, depending on the mechanism, which is generally greater than the radiative cooling timescale.…”
Section: Discussionmentioning
confidence: 99%
“…Proposed solutions in the framework of the canonical model include a complex sequence of luni‐solar resonances (Touma & Wisdom, ), resonant interactions between the Moon and the circumterrestrial disk (Ward & Canup, ), and encounters between large planetesimals and the newly formed Earth‐Moon system (Pahlevan & Morbidelli, ). Recently, Chen and Nimmo () and Ćuk et al () investigated inclination damping by lunar obliquity tides, and Ćuk et al () found that lunar inclination must have been large (∼30°) prior to the point in tidal recession where the lunar orbit transitions between Cassini states (distinct dynamical solutions that govern the alignment of the lunar spin axis and orbital plane, see Peale, ). Such a large inclination prior to the Cassini state transition defies explanation by any of the previously proposed mechanisms to raise lunar inclination after a canonical giant impact.…”
Section: Introductionmentioning
confidence: 99%
“…Ćuk and Stewart () showed that an evection resonance could drive significant AM loss from the Earth‐Moon system after the Moon‐forming impact. Since Ćuk and Stewart (), additional mechanisms have been found that could remove AM during lunar tidal evolution (Ćuk et al, ; Tian et al, ; Wisdom & Tian, ). Allowing for a change of AM after the impact significantly expands the range of possible impact parameters for the Moon‐forming collision.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations